UPAYA GURU DALAM MENINGKATKAN KARAKTER PROFIL PELAJAR PANCASILA PADA MATERI NILAI-NILAI PANCASILA SISWA KELAS V SEKOLAH DASAR - Subron Hadid; Asrial; Alirmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe teachers' efforts in improving the character profile of Pancasila students in Pancasila values material in elementary schools. This study was conducted at SDN 95/I Olak, Muara Bulian, with the research subjects being fifth-grade homeroom teachers. This study used qualitative phenomenology, which aims to understand the essence or nature of a teacher's experience in improving the character profile of Pancasila students. Data collection techniques included observation, interviews, and documentation. The results of the study show that teachers' efforts to improve the character profile of Pancasila students in learning Pancasila values include integrating Pancasila values into learning, applying active interactive learning methods such as group discussions and local wisdom projects, teachers also setting an example and providing direct examples to students, and creating a classroom environment that supports and values student development.